1996
DOI: 10.1007/bf02515734
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in female fertility related to interactions with flower consumers and pathogens in a forest metapopulation of Primula sieboldii

Abstract: Antagonistic biological interactions with flower consumers and pathogens may influence reproductive success of flowering plants, affecting population dynamics and natural selection for floral traits. However, ecological and evolutionary consequences of the interactions may depend on both spatial and temporal patterns of the interactions. In a forest metapopulation of Primula sieboldii E. Morren, an endangered clonal plant species, we measured between-subpopulation patterns of seed sets and interactions with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Our knowledge of how plants respond to herbivory comes primarily from experiments focusing on damage to nonreproductive tissue, even though petal damage can be quite severe with large consequences for plant Wtness in some populations (Washitani et al 1996;Wolfe 2002;Riba-Hernandez and Stoner 2005). In this study, I showed that both natural and artiWcial damage to reproductive tissues resulted in a variety of negative Wtness eVects in N. menziesii, but with little evidence of indirect eVects of damage.…”
Section: Discussionmentioning
confidence: 90%
“…Our knowledge of how plants respond to herbivory comes primarily from experiments focusing on damage to nonreproductive tissue, even though petal damage can be quite severe with large consequences for plant Wtness in some populations (Washitani et al 1996;Wolfe 2002;Riba-Hernandez and Stoner 2005). In this study, I showed that both natural and artiWcial damage to reproductive tissues resulted in a variety of negative Wtness eVects in N. menziesii, but with little evidence of indirect eVects of damage.…”
Section: Discussionmentioning
confidence: 90%
“…The reproductive success of Primula sieboldii largely depends on the availability of pollen mediated by queen bumblebees (Washitani et al . 1994b), and is influenced by antagonistic biological interactions, for example, with a flower consumer rove beetle and/or a specific smut fungal pathogen (Washitani et al . 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Bumblebees leave clear claw marks on flower petals, which can be used as an index of pollinator availability. As for antagonistic biotic agents, a flower consumer, a rove beetle, Eusphaleum usphaleum bosatsu Watanabe, and a specific smut fungal pathogen, Urocrystis tranzschelina (Lavrov) Zundel (Ustilaginales) have been shown to lower the female fertility of P. sieboldii (Washitani et al . 1996).…”
Section: Methodsmentioning
confidence: 99%